2021
DOI: 10.1007/s40265-021-01587-x
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density Loss and Fracture Risk After Discontinuation of Anti-osteoporotic Drug Treatment: A Narrative Review

Abstract: The number of patients on long-term anti-osteoporotic drug therapy is rising. Unfortunately, there are few data to guide decisions about duration of pharmacologic therapy for osteoporosis. Many practitioners discontinue therapy after a period of 5 years because of the risk of rare but severe side effects that may occur in long-term users. The objective of this narrative review was to describe the effects of discontinuation of anti-osteoporotic drugs and to investigate what is not yet known on this topic. For e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…It is not known whether discontinuation of the second, antiresorptive agent (usually a bisphosphonate, SERM or denosumab) induces the same effect as for the second drug used alone. In a recent narrative review of available clinical trials in which therapies were discontinued and followed up for a year or more, Elbers et al demonstrated 0.4% or lower decrease in femoral neck BMD after 1 year of discontinuation of therapy in both previously alendronate- and zoledronate-treated patients; hence in these patients a discontinuation of up to a year may be acceptable [ 108 ]. In the other reported agents (risedronate, ibandronate, raloxifene, teriparatide, denosumab and romosozumab) this percentage of bone loss at the femoral neck and total hip was at least 1%, with the largest decrease in BMD after discontinuation of denosumab and romosozumab, providing further support for the importance of continuation of antiresorptive agents after both agents [ 108 ].…”
Section: Long-term Treatment: Cycling Of Anabolic/antiresorptive Ther...mentioning
confidence: 99%
“…It is not known whether discontinuation of the second, antiresorptive agent (usually a bisphosphonate, SERM or denosumab) induces the same effect as for the second drug used alone. In a recent narrative review of available clinical trials in which therapies were discontinued and followed up for a year or more, Elbers et al demonstrated 0.4% or lower decrease in femoral neck BMD after 1 year of discontinuation of therapy in both previously alendronate- and zoledronate-treated patients; hence in these patients a discontinuation of up to a year may be acceptable [ 108 ]. In the other reported agents (risedronate, ibandronate, raloxifene, teriparatide, denosumab and romosozumab) this percentage of bone loss at the femoral neck and total hip was at least 1%, with the largest decrease in BMD after discontinuation of denosumab and romosozumab, providing further support for the importance of continuation of antiresorptive agents after both agents [ 108 ].…”
Section: Long-term Treatment: Cycling Of Anabolic/antiresorptive Ther...mentioning
confidence: 99%
“…Osteoporosis is a common disease characterized by the disturbance of bone homeostasis, which mainly threatens the health of postmenopausal women and the elderly 1 . At present, the main treatment means are oral drugs to delay the progression of bone loss, but the effect is relatively limited 2,3 . As the pathogenesis of osteoporosis is little known, there is an absence of acceptable grounds for drug design.…”
Section: Introductionmentioning
confidence: 99%
“…Discontinuation of osteoporosis therapy is followed by a decline of BMD ( 51 ). This is especially problematic after discontinuation of long-term treatment with denosumab, which results in a rapid decreased in BMD, rise and overshoot of bone turnover markers, and increase of fracture risk ( 52 ).…”
Section: Discussionmentioning
confidence: 99%